Mistreatment and violence against women during childbirth: a human rights issue (BioLaw Journal - Rivista di BioDiritto, 2023)
Mistreatment and violence against women during childbirth are not only a quality of care issue but a human rights issue (rights to life, health, bodily integrity, privacy, freedom from discrimination, respect for autonomy). The various forms of this phenomenon can occur at the individual level of the interaction between the woman and the provider as well as the structural level of the health facilities and systems; a definition that captures both these levels can help to adopt all measures to prevent and combat this phenomenon, and to modify laws, regulations and customs.
Keywords: Obstetric violence; human rights; respect for autonomy; informed consent; reproductive health services